A study on the differences level of general knowledge awareness among students in UiTM Melaka City Campus - Md. Kikar, Mohd. Zahirudin; Ahmad Nazari, Mazliana (2007)
General Knowledge is important for our daily life especially students. They should gain as much as they can for the purpose of their study and also for profession world. They need to realize that to be a high quality and competence student they should not depend on the knowledge that they gain during in classes only. This study tries to identify the effect of general knowledge towards student’s studies and also its importance, the objective of this research is to determine the relationship between variables and student awareness towards general knowledge. To identify the types of general knowledge that is popular among UiTM students. To determine the significance differences between the relationship of respondent profile with the student’s general knowledge awareness. To determine the significance differences between the relationships of types of general knowledge with the student’s general knowledge awareness. In order to conduct a reliable research, it has been conducted among a sample of 100 students from UiTM City Campus, Melaka from a population of almost 2000 students. Some methods such as frequencies, correlation, ANOVA and t-test have been used to analyze the data obtained from the respondents. As the result, we discover the relationship between the types of general knowledge, the importance and also attitude of students with the student’s general knowledge awareness. This study also provides some recommendation in improving the student’s general knowledge.